Demonization in International Politics A Barrier to Peace in the Israeli-Palestinian Conflict - Normand, Linn.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book investigates demonization in international politics, particularly in the Middle East. It argues that while demonization$1 (Bs origins are religious, its continued presence is fundamentally political. Drawing upon examples from historical and modern conflicts, this work addresses two key questions: Why do leaders demonize enemies when waging war? And what are the lasting impacts on peacemaking? In providing answers to these inquiries, the author applies historical insight to twenty-first century conflict. Specific attention is given to Israel and Palestine as the author argues that war-time demonization in policy, media, and art is a psychological and relational barrier during peace talks.s
Chapter 1: Introduction -- Chapter 2: Demonization in Historical Context -- Chapter 3: Demonization in War and Peace -- Chapter 4: The Israeli-Palestinian Conflict: An Introduction -- Chapter 5: Documenting Demonization in the Israeli-Palestinian Conflict -- Chapter 6: Demonization Deadlock in the Israeli-Palestinian Conflict -- Chapter 7: Conclusion.
Keywords: Political science; Political communication; Middle East -- Politics and government; Peace; Political sociology; Political Science and International Relations; Conflict Studies; Peace Studies; Middle Eastern Politics; Political Sociology; Political Communication; Electronic books